The dynamics of catastrophic and impoverishing health spending in Indonesia: how well does the Indonesian health care financing system perform? - Budi Aji; Mohammed, Shafiu; Haque, Md. Aminul; De Allegri, Manuela (Asia Pacific journal of public health, 2017)
Our study examines the incidence and intensity of catastrophic and impoverishing health spending in Indonesia. A panel data set was used from 4 waves of the Indonesian Family Life Surveys 1993, 1997, 2000, and 2007. Catastrophic health expenditure was measured by calculating the ratio of out-of-pocket payments to household income. Then, we calculated poverty indicators as a measure of impoverishing spending in the health care financing system. Head count, overshoot, and mean positive overshoot for each given threshold in 2000 were lower than other surveyed periods; otherwise, fraction headcount in 2007 of households were the higher. Between 1993 and 2007, the percentage of households in poverty decreased, both in gross and net of health payments. However, in each year, the percentages of households in poverty using net health payments were higher than the gross. The estimates of poverty gap, normalized poverty gap, and normalized mean positive gap decreased across the survey periods. The health care financing system performance has shown positive evidence for financial protection offerings. A sound relationship between improvements of health care financing performance and the existing health reform demonstrated a mutual reinforcement, which should be maintained to promote equity and fairness in health care financing in Indonesia.